2019
DOI: 10.1534/genetics.119.302494
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Full Distribution of Fitness Effects of New Amino Acid Mutations Across Great Apes

Abstract: The distribution of fitness effects (DFE) is central to many questions in evolutionary biology. However, little is known about the differences in DFE between closely related species. We use .9000 coding genes orthologous one-to-one across great apes, gibbons, and macaques to assess the stability of the DFE across great apes. We use the unfolded site frequency spectrum of polymorphic mutations (n = 8 haploid chromosomes per population) to estimate the DFE. We find that the shape of the deleterious DFE is striki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 76 publications
5
50
1
Order By: Relevance
“…This is consistent with the high rates of adaptive evolution observed in Drosophila (Smith & Eyre-Walker 2002;Andolfatto 2005;Eyre-Walker & Keightley 2009;Enard et al 2014) . Rates of adaptive evolution seem to be lower in humans than in Drosophila (Gossmann et al 2012;Galtier 2016;Rousselle et al 2019) which is therefore consistent with the fact that the slope is similar to the shape parameter of the gamma distribution recently estimated across great apes (Castellano et al 2019) .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is consistent with the high rates of adaptive evolution observed in Drosophila (Smith & Eyre-Walker 2002;Andolfatto 2005;Eyre-Walker & Keightley 2009;Enard et al 2014) . Rates of adaptive evolution seem to be lower in humans than in Drosophila (Gossmann et al 2012;Galtier 2016;Rousselle et al 2019) which is therefore consistent with the fact that the slope is similar to the shape parameter of the gamma distribution recently estimated across great apes (Castellano et al 2019) .…”
Section: Discussionsupporting
confidence: 88%
“…Second, we find that θ N /θ NC is negatively correlated to a measure of the effective population size of a window, θ NC /d NC . We find that the slope of the relationship in a log-log scale is consistent with the estimated shape parameter of the distribution of fitness effects in great apes (assuming the distribution is gamma distributed) (Castellano et al 2019) . This is in contrast to what has been observed in Drosophila melanogaster , in which the slope of the relationship between log(θ N /θ S ) versus log(θ S ) is significantly steeper than expected given an estimate of the DFE estimated from the site frequency spectrum; a similar pattern is apparent between species (Chen et al 2017;James et al 2017) .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Note that this interpretation relies on the assumption that different species from a given taxonomic group share the same DFE and, in particular, the same proportion of beneficial mutations. Castellano et al [40] compared the DFE across closely related species (great apes) and found that the deleterious DFE is quite stable across great apes, comforting us in our assumption that the DFE is expected to be similar between closely related species but different between distantly related species.…”
Section: Positive Relationship Between ω a And π S Among Closely-relasupporting
confidence: 57%
“…Moreover, a linear regression method can be used to infer the DFE from nucleotide diversity (James et al 2017). These approaches has been applied to numerous organisms, including plants (Chen et al 2017; Huber et al 2018; Chen et al 2020), Drosophila melanogaster (Keightley and Eyre-Walker 2007; Huber et al 2017; Castellano et al 2017; Barton and Zeng 2018; Johri et al 2020), and primates (Boyko et al 2008; Huber et al 2017;Kim et al 2017; Ma et al 2013; Castellano et al 2019).…”
Section: Introductionmentioning
confidence: 99%